2016
DOI: 10.9788/tp2016.1-04
|View full text |Cite
|
Sign up to set email alerts
|

Revisão da dimensão isolamento do inventário dimensional clínico da personalidade

Abstract: ResumoO presente estudo teve como objetivo revisar a dimensão Isolamento do Inventário Dimensional Clínico da Personalidade (IDCP). Para tanto, o método foi dividido em duas etapas, sendo a primeira voltada para elaboração de novos itens com base na literatura, e a segunda visou a verifi cação das propriedades psicométricas do novo conjunto de itens. O IDCP em conjunto ao Inventário de Personalidade NEO Revisado (NEO-PI-R) e o Personality Inventory for DSM-5 (PID-5) foram aplicados em uma amostra de 213 sujeit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
(13 reference statements)
0
6
0
3
Order By: Relevance
“…For the development of new items for the Eccentricity dimension, we verified the literature considered relevant in the pathological personality field, intended to understand the pathological manifestations of the underlying construct of the dimension, replicating previously procedures (Carvalho & Arruda, 2016;Carvalho & Sette, 2015;Carvalho & Sette, in press;Carvalho, Sette, & Ferrari, 2016;Carvalho, Sette, Capitão et al, 2014;Carvalho & Silva, 2016;Carvalho, Souza et al, 2014a, 2014b. We consult the Section 3 of the DSM-5 (APA, 2013a), the facets of the Personality Inventory for DSM-5 (PID-5) (Krueger, Derringer, Markon, Watson, & Skodol, 2012), the dimensions of the Shedler-Westen Assessment Procedure (SWAP-200) (Shedler & Westen, 2004) and the model of Clark (1990) that supports the Schedule for Nonadaptive Personality (SNAP).…”
Section: Methodsmentioning
confidence: 99%
“…For the development of new items for the Eccentricity dimension, we verified the literature considered relevant in the pathological personality field, intended to understand the pathological manifestations of the underlying construct of the dimension, replicating previously procedures (Carvalho & Arruda, 2016;Carvalho & Sette, 2015;Carvalho & Sette, in press;Carvalho, Sette, & Ferrari, 2016;Carvalho, Sette, Capitão et al, 2014;Carvalho & Silva, 2016;Carvalho, Souza et al, 2014a, 2014b. We consult the Section 3 of the DSM-5 (APA, 2013a), the facets of the Personality Inventory for DSM-5 (PID-5) (Krueger, Derringer, Markon, Watson, & Skodol, 2012), the dimensions of the Shedler-Westen Assessment Procedure (SWAP-200) (Shedler & Westen, 2004) and the model of Clark (1990) that supports the Schedule for Nonadaptive Personality (SNAP).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, we sought items that contributed to the prediction of people belonging to clinical groups, emphasizing the weight and significance of items in logistical regression analyses, and also which items showed greater difference in scores between the groups. It is noteworthy that partial analyzes were included (i.e., items from the original IDCP kept in the IDCP-2 and items that make up the Mood Instability dimension) in order to support these items in the final selection of the screening, given the quality of the items kept in the IDCP-2 (e.g., Carvalho, & Arruda, 2016;Carvalho, Pianowski, & Miguel, 2015;Carvalho, & Sette, 2015;2017;Carvalho, Sette, Capitão, & Primi, 2014;Carvalho, Souza, & Primi, 2014) and in the suitability of the content of Mood Instability in the identification of symptoms of PDs (e.g., Abela et al, 2015;Carvalho & Primi, 2016). The first group of analyses, using 147 items of the IDCP, pointed out a group of 31 items as more discriminative.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that for the first regression analysis, with all the items, only the forward method (wald) was used, since many predictor variables were inserted. The analysis covering only the 61 items kept between the IDCP and its revised version, IDCP-2, was performed considering that (a) the items kept in the revised version are empirically those which presented higher psychometric adequacy in previous studies (e.g., Carvalho & Arruda, 2016;Carvalho, Pianowski, & Miguel, 2015;Carvalho, & Sette, 2015;, 2017;Carvalho, Sette, Capitão, & Primi, 2014;Carvalho, Souza, & Primi, 2014) and (b) despite some items shared with the analysis covering the IDCP in general, it is a different grouping of predictive variables. Similarly, in the third group of analyses, only the 27 items composing the Mood Instability dimension were used, since data presented in previous studies suggested this dimension as subjacent to pathological personality functioning in general (e.g., Abela, Carvalho, Cho, & Yazigi, 2015;Carvalho, & Primi, 2016;.…”
Section: Methodsmentioning
confidence: 99%
“…Psychometric properties of the dimensions, evidence of validity (based on the internal structure and external variables) and reliability indices (for internal consistency) have been shown to be appropriate in studies that provide a basis for the IDCP-2. 19,[23][24][25][26][27] For the present study, we used the revised version of the criticism avoidance dimension, 19 which contains 18…”
Section: Instrumentsmentioning
confidence: 99%